2010
DOI: 10.1055/s-0029-1240925
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes following Repair or Replacement in Degenerative Mitral Valve Disease

Abstract: MVP is superior to MVR for the treatment of degenerative MR despite the impact of repair failure. Age less than 60 years, ring size to body surface area greater than 19.0, absence of a prosthetic ring and residual MR at the end of surgery (≥ 1/4) reduce the durability of MVP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
0
27
0
3
Order By: Relevance
“…Better preoperative NYHA classification and ejection fraction have been shown to be very strong predictors of survival. In the majority of the studies, ejection fraction was not significantly different, however NYHA status was better in half of the studies in the MVP group [19-22]. Additionally, age and female gender have also been shown to be poor predictors of post-operative outcomes including survival [23-27].…”
Section: Methodsmentioning
confidence: 99%
“…Better preoperative NYHA classification and ejection fraction have been shown to be very strong predictors of survival. In the majority of the studies, ejection fraction was not significantly different, however NYHA status was better in half of the studies in the MVP group [19-22]. Additionally, age and female gender have also been shown to be poor predictors of post-operative outcomes including survival [23-27].…”
Section: Methodsmentioning
confidence: 99%
“…15) Five-year-survival rates of degenerative mitral valve patients are given for repair and replacement patients as 84.3% and 64.6% respectively. 6) Many studies have showed that repair is better than replacement in terms of operative mortality, morbidity, survival, endocarditis and thromboembolic complications. 13,14) Although the reoperation ratios are suggested to be similar, there are studies referring to high reoperation ratios in the ischemic mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Although thromboembolic complications in the mechanical valves and early degeneration of biological valves were the major disadvantages of mitral valve replacement (MVR), due to the high achievement drive of the method in terms of early post-surgical rehabilitation, it was used as the preferred method in the mitral valve surgery for many years. [5][6][7] However, during the last ten years, thanks to the better standardized rehabilitation techniques, surgeons gained experience and in this way mitral valve repair (MvRp) has become the preferred method in mitral valve surgery. 5,6) The success of the mitral operations has increased due to the standardization of surgical techniques and comprehensive post-operative intensive care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations